Transformation of Student Character Building through Religious-Based Child-Friendly School Programs: Responding to Challenges and Creating Sustainable Character Education Solutions - Fathan Fahmi; Aunur Rofiq; Indah Aminatuz Zuhriyah (Al-Qalam Institute, 2024)
This study explores the implementation of a religious-based Child-Friendly School Program (SRA) at MTs. Almaarif 01 Singosari and its influence on the development of student character. The research investigates how the integration of religious values, positive discipline policies, and the active involvement of parents and school committees contribute to shaping students' behavior. The study is motivated by the ongoing challenges in character education, particularly the need for a holistic approach that blends academic learning with moral and spiritual development. Using a qualitative case study methodology, the research employs data collection methods such as observations, interviews, and document analysis. Key informants include school administrators, teachers, students, parents, and school committee members, providing a comprehensive view of the program’s impact. The findings reveal that the SRA program has effectively created a supportive environment for character building, with significant contributions from the school’s discipline policies and the involvement of all stakeholders. The program has led to improvements in student behavior, including increased discipline, responsibility, and respect for religious values. This research highlights the importance of integrating character education with religious teachings and demonstrates how collaborative efforts among educators, parents, and the community can foster a well-rounded educational environment. The findings have broader implications for the development of similar programs in other educational contexts, particularly in promoting moral and spiritual growth among students.